2006
DOI: 10.1111/j.1365-294x.2005.02830.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferring colonization history from analyses of spatial genetic structure within populations of Pinus strobus and Quercus rubra

Abstract: Many factors interact to determine genetic structure within populations including adult density, the mating system, colonization history, natural selection, and the mechanism and spatial patterns of gene dispersal. We examined spatial genetic structure within colonizing populations of Quercus rubra seedlings and Pinus strobus juveniles and adults in an aspen-white pine forest in northern Michigan, USA. A 20-year spatially explicit demographic study of the forest enables us to interpret the results in light of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 83 publications
5
62
0
Order By: Relevance
“…Indeed, the genetic differentiation we observed falls within the range of values reported for geographically isolated populations, or across species' ranges, in the southwest region and that are attributed to isolation by distance effects (Bradbury et al, 2013b;Nistelberger et al, 2015). Alternatively, high population genetic differentiation may reflect colonisation or recruitment history (Jones et al, 2006;Pardini and Hamrick, 2008). For example, in Albizia julibrissin (Fabaceae), different genetic groups were Pollen dispersal in a bird-pollinated eucalypt N Bezemer et al spatially and temporally clustered and corresponded to episodes of recruitment (Pardini and Hamrick, 2008).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Indeed, the genetic differentiation we observed falls within the range of values reported for geographically isolated populations, or across species' ranges, in the southwest region and that are attributed to isolation by distance effects (Bradbury et al, 2013b;Nistelberger et al, 2015). Alternatively, high population genetic differentiation may reflect colonisation or recruitment history (Jones et al, 2006;Pardini and Hamrick, 2008). For example, in Albizia julibrissin (Fabaceae), different genetic groups were Pollen dispersal in a bird-pollinated eucalypt N Bezemer et al spatially and temporally clustered and corresponded to episodes of recruitment (Pardini and Hamrick, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, the three genetic clusters of E. caesia were interspersed rather than aggregateda pattern that we suggest reflects gradual erosion of spatial genetic structure through extensive pollen dispersal and subsequent recruitment of widely outcrossed individuals, and a high survivorship of adult plants through lignotuber resprouting. On the other hand, weak spatial structuring of genetic groups could also reflect long-distance seed dispersal or the historical effect of a seed shadow (Jones et al, 2006). Spatial autocorrelation analysis indicated genetic patch sizes of 70 m in the study population that may partially reflect greater seed dispersal distances than expected for eucalypts as seeds may be transported downslope by wind or water (Byrne and Hopper, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…They account for the speed of recolonization of Europe by tree species during the last post-glacial period (Austerlitz & Garnier-Gere 2003;Bialozyt et al 2006). At small spatial scales, only few studies have directly examined the connection between colonization events and plant population genetics (Ingvarsson & Giles 1999;Erickson et al 2004;Litrico et al 2005;Sezen et al 2005;Jones et al 2006;Raffl et al 2006;Yang et al 2008), and these have supported a causal relationship between the ecological circumstances of colonization and genetic diversity and population differentiation. Among them, most studies concerning large woody species (shrubs and trees) evidence (i) a major role of long dispersal mixing founders from multiple sources, (ii) combined with genetic homogeneity among sources due to gene flow, and (iii) the importance of the accumulation of new colonists during the juvenile phase of the first colonists (Erickson et al 2004;Litrico et al 2005;Yang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even in the context of common long-distance pollen flow in plant species, spatial genetic structure (SGS) due to isolation-by-distance (IBD) processes is generally observed (Vekemans & Hardy 2004). This is generally assumed to be due to some short-distance (or, exceptionally, aggregated sibling dispersal; Jones et al 2006) seed dispersal resulting in the presence of half-siblings close to their maternal parents.…”
Section: Introductionmentioning
confidence: 99%
“…Within forest tree populations, the common trend of increased heterozygosity in older age classes is considered as an indicator of previous selection against inbred individuals in younger age classes (Shaw and Allard, 1982;Farris and Mitton, 1984;Yazdani et al, 1985;Marquardt and Epperson, 2004;Jones et al, 2006). Some studies have shown increasing heterozygosity with age, suggesting that a rapid purging of inbred individuals occurs in these classes (Pichot et al, 2006).…”
Section: Introductionmentioning
confidence: 99%